Barriers and Facilitators of Self-Management Among Older Adults with Knee Osteoarthritis in Thailand - Noppakhun, Thichatthaya; Chiangkhong, Araya (The Journal of Behavioral Science, 2023)
Knee osteoarthritis (KOA) is a chronic condition that significantly impacts the quality of life for older adults who lack adequate care or fail to engage in appropriate self-management practices. This study explored the perceptions of older adults with KOA in Thailand concerning the barriers and facilitators associated with self-management strategies designed to reduce the severity of knee osteoarthritis. This qualitative research employs a case study approach involving 10 older adults residing in Thailand, selected through purposive sampling. In-depth interviews were conducted using semi-structured interview guidelines. The interviews were transcribed verbatim and continued until data saturation was achieved. Data were analyzed using content analysis. The results showed that eight primary themes served as both barriers and facilitators in reducing the severity of KOA. These barriers included physical problems, lack of motivation, lack of time, and unsuitable environment, while the facilitators encompassed knowledge about weight control, social support, hope for good health, and accessible exercise opportunities. These findings offered valuable insights into the specific challenges and facilitators that affected self-management among older adults with KOA, guided the development and implementation of targeted interventions to enhance their self-management activities, and contributed to the theoretical knowledge in behavioral science. This will serve as a reference for improving self-management practices among these patients and support primary healthcare efforts to prevent the severity of KOA.